Vital yet vulnerable: Mental and emotional health of South Asian migrant Workers in Singapore - HARRIGAN, Nicholas (Institutional Knowledge at Singapore Management University, 2015)
Numbering nearly one million persons, low-waged, low-skilled migrant workers are a vital yet vulnerable part of Singapore’s economy and society. This study, undertaken several months before the Little India riots of December 2013, measures the psychological distress of 261 South Asian Work Permit holders, and 344 South Asian injury and salary claim workers. While most regular Work Permit holders are relatively happy and healthy, our study finds that 62 per cent of injury and salary claim workers meet the screening conditions for a Serious Mental Illness. We find that the three main drivers of psychological distress are (1) the housing problems of injury and salary claim workers, (2) threats of repatriation against both injured and regular workers, and (3) agent fee debt. We recommend a range of policy options to address these problems, including alternative housing for injury and salary claim workers; delinking Work Permit holders’ visas and employment contracts; and regulation of offshore migration agents.